To simplify the expression \( 25(34p + 56w) + 15(12p - 623w) \), we can start by distributing the coefficients \( 25 \) and \( 15 \) to the terms within the parentheses.
-
Distributing \( 25 \): \[ 25(34p) + 25(56w) = 850p + 1400w \]
-
Distributing \( 15 \): \[ 15(12p) + 15(-623w) = 180p - 9345w \]
Now, we combine the results from both distributions: \[ 850p + 1400w + 180p - 9345w \]
Next, we combine the like terms for \( p \) and \( w \):
For \( p \): \[ 850p + 180p = 1030p \]
For \( w \): \[ 1400w - 9345w = 1400 - 9345 = -7945w \]
Bringing it all together, the simplified expression is: \[ \boxed{1030p - 7945w} \]